FUNDAMENTALISME AGAMA : Telaah Artikel “Religious Fundamentalism” dalam Buku Introducing Anthropology of Religion; Culture of the Ultimate Karya Jack David Eller - Nur Kholis (Fakultas Ilmu Budaya Universitas Diponegoro, 2018)
The discussion in the article